Сім’ї трудових мігрантів: соціально-побутові умови життя дітей після від’їзду батьків - Демчук, Станіслав Петрович; Демчук, Станислав Петрович; Demchuk, Stanislav P. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Наслідком збільшення кількості тимчасових трудових мігрантів у країнах Центральної та Східної Європи, окрім відтоку робочої сили, є утворення дискантних сімей. Зазначена проблема актуалізувала розв’язання завдань щодо аналізу причин трудової міграції, впливу феномену трудової міграції на інститут сім’ї, механізму соціалізації підлітків у дискантних сім’ях. Виведено взаємозалежність між відсутністю батьків (трудових мігрантів) та відхиленням у міжособистісних стосунках, формуванням певних проблем соціально-психологічного характеру, пасивною соціальною позицією дітей трудових мігрантів. Установлено, що трудова міграція – одна з причин руйнації сімейних відносин і викривлення механізму соціалізації; фактор, що підвищує ризик еміграції. The number of temporary working migrants recently increased in the countries of Central and Eastern Europe including Ukraine. As a result, apart from the labour force flow-out, quite a serious problem has arisen – the formation of distant families, in which principles of healthy and nuclear family functioning are violated. The abovementioned problem made topical solving of the tasks concerning the analysis of labour migration motives, the influence of labour migration phenomenon on the family institution, teenagers’ socialization mechanism in distant families. In the article the interrelation between the parents’ (working migrants’) absence and deviation in interpersonal relationships, the formation of certain social- psychological problems, and passive social attitude of the working migrants’ children is concluded. A conclusion is made as to the labour migration being one of the reasons to ruin family relationships and to distort socialization mechanism as well as the factor to increase the emigration risk.
Families of Migrant Workers: the Social and Living Conditions of Children by their Parents Away
Keywords: діти трудових мігрантів; інститут сім’ї; трудова міграція; соціально-психологічне здоров’я; соціалізація; children of migrant workers; the institution of the family; labor migration; social and psychological health; socialization